The Relationship Between Literacy and Numeracy Skills of Prospective Primary Education Teachers - Ratnaya, I Gede; Fitriani, Siti Nurul; Durasa, Helfa; Erlin, Erlin (Departemen Pendidikan Guru Madrasah Ibtidaiyah Fakultas Tarbiyah dan Keguruan Universitas Islam Negeri Antasari Banjarmasin, 2024)
Literacy and numeracy have become prerequisites for society to improve competence in social life. This research endeavor seeks to establish the correlation between the literacy components found in informational texts and literary texts and their impact on numeracy proficiency. This study involved 207 prospective primary education teachers of the Teacher Education Faculty of Tarbiyah Hamzanwadi Pancor Islamic Institute as the study population. The sampling technique used simple random sampling, so 78 prospective primary education teachers were obtained as research samples. The research findings show that there is a simultaneous relationship between literacy skills in the aspects of informational texts and literary texts with numeracy skills in prospective primary education teachers, Faculty of Tarbiyah, Hamzanwadi Islamic Institute Pancor. The contribution of literacy influence is 52% to increase numeracy ability. In addition, literacy skills in aspects of information texts and aspects of literary texts also partially affect the improvement of numeracy skills in students.